Different Approaches to Assess the Seismic Capacity of Masonry Bridges by Non-linear Static Analysis - Zampieri, Paolo; Perboni, Simone; Tetougueni, Cyrille Denis; Pellegrino, Carlo (Frontiers in Built Environment, 2020)
A large portion of the existing masonry arch bridges in Italy are still in service in the infrastructure system and are located in a high seismic risk geographical area. They were mainly built more than 100 years ago taking into account only gravitational loads during the design phase without any seismic analysis. For this reason, a seismic vulnerability assessment is mandatory from the Italian government in order to define the priority of seismic retrofit interventions. In this study, a multi-span slender masonry bridge considered as the most vulnerable typology of masonry bridges to seismic action will be assessed. Then, the results obtained from three different seismic assessment approaches will be discussed and compared. In particular, two approaches based on different FE modelling and the last one built on rigid block analysis are considered. Finally, a detailed 3D finite element analysis allowed representing all the collapse mechanism (global and local) of the bridges are presented. Simplified approaches, even though cannot describe all the collapse mechanisms of the bridges due to seismic action can lead to reliable results.